Role of Ba in engineering band gap, photoluminescence and nonlinear optical properties of SnO2 nanostructures for photovoltaic and photocatalytic applications. (October 2018) - Bannur, M.S.; Antony, Albin; Maddani, K.I.; Poornesh, P.; Manjunatha, K.B.; Kulkarni, Suresh D.; Choudhari, K.S.
Abstract: In this article, we present the role of Ba doping in tuning energy gap, photoluminescence (PL) and third-order optical nonlinearity χ (3) of SnO2 nanostructures. Surface morphology analysis indicates the fragmentation of larger grains upon Ba incorporation possibly caused by the lattice mismatch effects. X-ray diffraction reveals polycrystalline nature of the nanostructures with rutile tetragonal structure. A shift in preferential growth orientation plane (200, 211, 110) has been observed with increase in Ba concentration. PL spectroscopy studies confirms the crystallinity of the films ruling out the presence of Sn interstitials. The green luminescent center at 550 nm and trap emission at 578 nm are attributed to singly ionized charge state of the oxygen and defect levels in band gap. Relatively large change in the band gap (3.64 eV −3.13 eV) arises due to Ba doping points the credibility of SnO2 thin films for use in photovoltaic and photocatalytic applications. Third-optical nonlinearity of the films investigated by Z-scan technique shows χ (3) as high as 3.37 × 10 −3 esu indicating the suitability of SnO2 nanostructures in nonlinear optical (NLO) devices such as optical power limiters and switches. Highlights: X-ray diffraction reveals rutile tetragonal structure of Ba:SnO2 nanostructure. Large change in band gap upon Ba doping points the credibility of SnO2 nanostructures in photovoltaic applications. Green luminescent center at 550 nm and trap emission at 578 nm were detected from PL spectra. Ba:SnO2 nanostructures shows χ (3) as high as 3.37 × 10 −3 esu.